2014
DOI: 10.1016/j.tiv.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates cisplatin renal cortical cytotoxicity by modifying oxidative stress

Abstract: Cisplatin, a cancer chemotherapy drug, is nephrotoxic. The aim of this study was to investigate whether resveratrol (RES) reduced cisplatin cytotoxicity and oxidative stress. Rat renal cortical slices were pre-incubated 30 min with 0 (VEH, ethanol) or 30 μg/ml RES followed by 60, 90 or 120 min co-incubation with 0, 75, or 150 μg/mL cisplatin. Lactate dehydrogenase (LDH) leakage was unchanged at 60 and 90 min by cisplatin. Cisplatin increased (p<0.05) LDH leakage at 120 min which was protected by RES. Cisplatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 42 publications
7
41
0
Order By: Relevance
“…Also, administration of resveratrol led to decrease in glutathione depletion and lipids peroxidation. 15,16 Resveratrol also shows anti-inflammatory properties and suppresses oxygen species activity and its antioxidant property is linked with declined 4-HNE (4-hydroxynonenal) and carbonyl-adduction, 15 thus it is concluded that its nephroprotective action is due to its reported anti-oxidant potential. Another study reported, was carried out on rats which demonstrated an increase in levels of serum creatinine, urine protein and volume, lipids peroxidation and glutathione depletion in cisplatintreated rats.…”
Section: Resveratrolmentioning
confidence: 99%
“…Also, administration of resveratrol led to decrease in glutathione depletion and lipids peroxidation. 15,16 Resveratrol also shows anti-inflammatory properties and suppresses oxygen species activity and its antioxidant property is linked with declined 4-HNE (4-hydroxynonenal) and carbonyl-adduction, 15 thus it is concluded that its nephroprotective action is due to its reported anti-oxidant potential. Another study reported, was carried out on rats which demonstrated an increase in levels of serum creatinine, urine protein and volume, lipids peroxidation and glutathione depletion in cisplatintreated rats.…”
Section: Resveratrolmentioning
confidence: 99%
“…Capsaicin potentiates the apoptotic activity of cisplatin in human stomach cancer and attenuates cisplatin-induced renal toxicity in rodent models [11, 12]. …”
Section: Pharmacological Effects Of Capsaicinoidsmentioning
confidence: 99%
“…CP reacts with nucleophilic sites in DNA, forming monoadducts as well as intra and interstrand cross‐links . Different mechanisms have also been reported describing the pathogenesis of CP toxicity out of which oxidative stress appears to play an important role . The accumulated CP enters the cell and causes disturbance to the redox status either by reducing the endogenous antioxidants, such as GSH and NADPH or by damaging the mitochondrial inner membrane which releases free radicals such as reactive oxygen species (ROS) and reactive nitrogen species (RNS).…”
Section: Introductionmentioning
confidence: 99%
“…Anticarcinogenic impacts of polyphenolic compounds in fruits and vegetables are well established. Ellagic acid (EA) [2,3,7,8-tetrahydroxy (1) benzopyrano (5,4,3,-cde) (1)benzopyran-5,10-dione) is one such polyphenol phytochemical present in a variety of foods. It has been proven that EA, when given in conjunction with chemotherapeutic drugs, augments their therapeutic effect.…”
mentioning
confidence: 99%